Exploring Sleep Patterns in 3,475 College Students: A Comparative Study of Geographical Location, Gender, and Age - Moussa-Chamari, Imen; Romdhani, Mohamed; Farooq, Abdulaziz; Trabelsi, Khaled; Yousfi, Narimen; Kamoun, Karim; Ahmadian, Arezou; Almarri, Senaid Salem; Chamari, Karim; Hue, Olivier (Sleep Science, 2024)
Objective Sleep is a fundamental physiological process essential for maintaining overall health and optimal functioning across various cognitive, emotional, and physical domains. To cross-sectionally investigate the sleep pattern among college students according to geographical location, gender, and age.Materials and Methods A total of 3,475 valid responses, 3,366 from 4 continents (Africa – n = 1,095; America – n = 182; Asia – n = 1,562; Europe – n = 527); 2,075 from female students and 1,369 from male students (n = 3,444), were analyzed. Sleep quality, insomnia, and daytime sleepiness were assessed using validated questionnaires (Pittsburgh Sleep Quality Index [PSQI], Insomnia Severity Index [ISI], and Epworth Sleepiness Scale [ESS], respectively).Results Students from all continents had poor sleep quality, and there were inter-countries differences in sleep quality. The frequency of poor sleep quality and subclinical-to-clinical insomnia were higher among Asian (AsiS) and African students (AfS) compared with American (AmS) and European students (EuS) (p < 0.05). Asian students had a greater frequency of excessive daytime sleepiness (EDS) compared with those from other continents (p < 0.05). Females showed higher mean ISI scores (p < 0.001) as well as a greater frequency of poor sleep quality (p < 0.05), subclinical-to-clinical insomnia (p < 0.05), and EDS (p < 0.05) compared with males. Insufficient sleep duration was more frequent in older-aged groups (i.e., 26–30, 31–35, and > 36 years) compared with the ≤ 20 years age group (p < 0.05). Excessive daytime sleepiness was more frequent in younger age groups (i.e., ≤ 20 and 21–25 years) versus the > 36 years (p < 0.05) group. There were no significant differences in the frequency of various degrees of insomnia across age groups.Conclusion Our results suggest the need for tailored interventions for addressing sleep disturbances among college students of all age groups, with a specific focus on AsiS and AfS, as well as female students.
Keywords: community survey; continental population group; Insomnia disorder; Sleeplessness